AL-Gunyah : Mencari jalan kebenaran / Syaikh Abdul Qadir Al-Jailani; penerjemah, Ustadz Masrohan Ahmad; editor, Supariyanto Abdullah - ABDUL QADIR AL-JAILANI, Syaikh; Musrohan Ahmad, Ustadz.; Supriyanto Abdullah (Citra Risallah, 2010)
xviii, 460 hlm. . ilus. ; 24 cm (3 eks)